S22 Risk factors and secondary care utilisation in a primary care population with nontuberculous mycobacterial disease in the UK. (December 2018) - Bual, N; Axson, EL; Bloom, CI; Quint, JK
Abstract : Introduction and objective: Prior research has identified risk factors associated with developing nontuberculous mycobacterial disease (NTMD) 1 ; we identified risk factors and secondary care utilisation of NTMD patients in the UK. Methods: This was a matched case-control study using electronic healthcare records from the Clinical Practice Research Datalink from 2006–2016. NTMD was defined using prescription data and Read codes, based on international guidelines. 2 Risk factors for NTMD were investigated using conditional logistic regression within a general population and a chronic respiratory diseases subpopulation (CRDs: asthma, bronchiectasis, COPD, interstitial lung disease and cystic fibrosis). All-cause secondary care utilisation (combined inpatient, outpatient, emergency visits) was investigated for participants with linked Hospital Episode Statistics (HES), using incidence rate ratio (IRR) from 2007–2015. Results: We identified 1225 individuals with NTMD, 463 with underlying CRD. A subset of individuals (426 general; 163 CRD) were eligible for linkage with HES. In the general population adjusted model, risk factors associated with an increased likelihood of NTMD included being underweight (odds ratio (OR): 2.92; 95% CI: 1.95, 4.36); bronchiectasis (OR: 23.3; 12.4–43.9); COPD (OR: 2.47; 1.69–3.62); chronic kidney disease (OR: 3.07; 2.21–4.27); lung cancer (OR: 14.9; 3.98–55.7); diabetes (OR: 1.54; 1.14–2.08); previous tuberculosis (OR 69.0; 47.7–99.8); rheumatoid arthritis (OR: 2.12; 1.05–4.27); immunosuppressive (excluding corticosteroids) medication (OR: 3.05; 1.15–8.10); inhaled corticosteroids (OR: 1.51; 1.07–2.14); and oral corticosteroids (OR: 7.28; 4.94–10.7) (figure 1). CRD population adjusted risk factors included being underweight (OR: 4.70; 2.58–8.55); bronchiectasis (OR: 6.88; 4.46–10.6); lung cancer (OR: 8.83; 2.59–30.1); previous tuberculosis (OR: 36.1; 21.7–60.2); rheumatoid arthritis (OR: 2.49; 1.04–5.97); immunosuppressive (excluding corticosteroids) medication (OR: 9.23; 2.12–40.1); inhaled corticosteroids (OR: 1.52; 1.11–2.08); and oral corticosteroids (OR: 6.17; 4.17–9.13) (figure 1). NTMD patients had significantly higher rates of secondary care utilisation than non-NTMD patients (general IRR: 5.80; 5.14–6.46); CRD IRR: 3.26; 2.89–3.62). Conclusions: Previous tuberculosis, bronchiectasis, immunosuppressive medication and OCS increased odds of NTMD the most within the general and CRD populations. NTMD increased secondary care utilisation in both populations. References: Andréjak C. doi:10.1136/thoraxjnl-2012-201772 Axson EL. doi:10.1007/s10096-018-3315-6